Rekognisi dan Reposisi Aktor dalam Asimilasi Hukum Lama di Nagari (Baru) Sumatera Barat - Aulia Rahmat (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
Nagari as a system of local wisdom that lives in the Minangkabau society has a long way in it relation to national law and international values, especially in the era of transnationalization of law. The regulations have been always led to a shifted the structure and function of the customary government structure in Minangkabau. This article is an evaluation of existing Nagari Government regulations in West Sumatra. The paradigm used is constructivist with a socio-legal approach. The result indicate that there is a shift in the order, structure, and function of cultural actors in society in the established local laws. The formation of local laws regarding Nagari as a response to the opportunities provided by the Village Law reaffirms the independence of the nagari through the existence of the Adat Salingka Nagari. The discussion to results leads to the use of the old legal assimilation in the legislation of Nagari Regulation has not succeeded to present a representative local law in protecting local wisdom in West Sumatra. So it is deemed necessary to minimize the state's domination of the people's needs in creating a balanced and comprehensive democracy.